State university faculty performance-based evaluation system with data graph analysis - Mandia, Jonathan; Pomperada, Phd., Jake; Madrigal, Dennis V (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study presents the design and development of a State University Faculty Performance-Based Evaluation System with Data Graph Analysis, aimed at addressing the limitations of traditional and semi-digital evaluation methods used in higher education institutions. Existing systems, such as manual evaluations and third-party tools like Google Forms, often suffer from inefficiency, limited data analysis, and issues in confidentiality and accessibility. The proposed system integrates a centralized database, secure two-factor authentication, dynamic questionnaires, automated report generation, and stakeholder-specific dashboards to streamline faculty evaluations. A key innovation is the incorporation of data graph analysis, enabling administrators to visualize performance trends, identify strengths and weaknesses, and make evidence-based decisions on faculty development, research, and extension activities. The system was evaluated using usability, reliability, interactivity, and security criteria, yielding excellent results based on stakeholder testing. By institutionalizing a secure, transparent, and data-driven evaluation process, this project provides a sustainable framework for enhancing faculty performance management and supporting continuous academic improvement in State Universities and Colleges. In addition, the system ensures compliance with data privacy requirements by securing sensitive information through advanced authentication and backup mechanisms. Its user-friendly interface and responsive design allow accessibility across multiple devices, promoting inclusivity among stakeholders such as students, peers, supervisors, and administrators. The generated visual reports serve as a valuable reference for policy formulation, strategic planning, and targeted faculty training. Furthermore, the project emphasizes the importance of shifting from compliance-based evaluation toward a culture of continuous improvement, accountability, and innovation. Overall, this capstone underscores the role of technology-driven evaluation systems in shaping quality assurance and academic excellence in higher education.